2018
DOI: 10.1049/iet-nbt.2016.0260
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Fe/SDS and Au nanoparticles on P. aeruginosa bacterial growth and biosurfactant production

Abstract: The aim of this study was to evaluate the effects of iron (Fe)/SDS and gold (Au) nanoparticles on growth and biosurfactant production of . The concentrations of the nanoparticles used were 1, 500 and 1000 mg/l. In this research, the surface tension of biosurfactant, dry weight of biosurfactant and biomass, emulsification indexes (E) were measured and transmission electron microscopy analysis was used to monitor the nanoparticles. The test results showed that the effect of nanoparticles on the bacterial growth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…3 and 4). Alamdar, Rasekh & Yazdian (2018) reported increase in growth and biosurfactant production when bacterial strains were treated with SDS nanoparticles at a concentration of 1 mg/ml and have shown no side effect at this concentration. Ethylenediaminetetraacetic acid also improved auxin production potential.…”
Section: Discussionmentioning
confidence: 94%
“…3 and 4). Alamdar, Rasekh & Yazdian (2018) reported increase in growth and biosurfactant production when bacterial strains were treated with SDS nanoparticles at a concentration of 1 mg/ml and have shown no side effect at this concentration. Ethylenediaminetetraacetic acid also improved auxin production potential.…”
Section: Discussionmentioning
confidence: 94%
“…Several studies investigated the effect of different nanoparticles on the rate of biosurfactant production by different bacteria [59, 60]. The research of Alamdar et al., showed that, the effect of nanoparticles on the bacterial growth and biosurfactant production varied corresponding to the type and concentration of nanoparticles [50]. In this study, effect of starch‐coated Fe 0 and Fe 3+ nanoparticles on the biomass and biosurfactant production of B. subtilis was investigated.…”
Section: Discussionmentioning
confidence: 99%
“…In the similar study, the effect of Fe/SDS and Au nanoparticles on growth rate and biosurfactant production for application in oil industry was investigated. The results showed that low concentrations of nanoparticles Fe/SDS and Au have positive effects on bacterial biosurfactant production and suggested that they could serve as a good alternative to chemical surfactants for petroleum industry [50].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have shown that NPs can improve antimicrobial, anticorrosion, and antitumor functionalities through silver NPs [17], copper NPs [1, 18], and LDH NPs [19]. Moreover, other studies have shown that NPs can improve the growth of bacterial cells and their production of metabolites [2022]. Specifically, NP aggregates can attach to and/or entrap cells, thereby impacting their cellular functions.…”
Section: Introductionmentioning
confidence: 99%